Low complexity hybrid SLM for PAPR mitigation for ACO OFDM - Roland Niwareeba; Mitchell A. Cox; Ling Cheng (ICT Express, 2022)
The high peak to average power ratio (PAPR) is the main challenge facing asymmetrically clipped optical (ACO) orthogonal frequency division multiplexing (OFDM). We propose a new hybrid technique that incorporates a modified selective mapping (SLM) and companding called low complexity hybrid selective mapping (LCHSLM) for PAPR mitigation in ACO OFDM systems. It is demonstrated through computer simulations that our proposed system significantly reduces the PAPR compared with the conventional SLM or companding alone. In addition, LCHSLM achieves a significant reduction in complexity compared with conventional SLM without bit error rate (BER) degradation.